A qualitative study on parents' reasons and recommendations for childhood vaccination refusal in Malaysia - Jolyn Rumetta; Haireen Abdul-Hadi; Yew-Kong Lee (Elsevier, 2020)
Background: Vaccine-related diseases are increasing in developing countries. This study aimed to explore parents' reasons for refusal of childhood vaccinations in Malaysia and their recommendations on addressing their concerns. Methods: A qualitative study design involving individual both face-to-face and online in-depth interview was used. The topic guide was developed from the Health Belief Model theoretical framework. Seven face-to-face and seven online interviews were conducted with parents in the Klang Valley (an urban area) who had refused childhood vaccination. All interviews were audio-recorded, transcribed verbatim and checked. Thematic approach was used to analyze the data. Data was collected until data saturation was reached. Results: Findings were summarized into two main categories: Personal Health Beliefs and Vaccine Related Concerns. Six personal health beliefs were identified: lack of confidence in modern medicine and health care personnel, pharmaceutical conspiracy to sell medicines, preference to a natural approach to health, personal instincts, religious beliefs and having a partner with similar beliefs. Four main vaccine-related concerns were identified: negative effects and content concerns, doubts of necessity and lack of information and knowledge regarding vaccines. Parents recommended that more empathy from healthcare professionals and evidence on safety and content purity would help them reconsider vaccination. Conclusion: Parents had multiple reasons for refusing childhood vaccinations but felt that communication and empathy from healthcare professionals was lacking. Besides individual consultations with parents, addressing these concerns at multiple levels in the health care system and society may help to increase the uptake of childhood vaccinations in the future. Keywords: Primary health care, Vaccines, Treatment refusal